Penguatan Literasi pada Siswa Sekolah Menengah Atas Negeri 1 Amanuban Selatan - Cornelia Amanda Naitili; Lanny I.D. Koroh; Jhon Enstein; Viktorius P. Feka; Kristina E. Noya Nahak; Femberianus Sunario Tanggur (FKIP Universitas Citra Bangsa, 2024)
Literacy activities in learning aim to develop the ability to understand texts and relate them to personal experiences, think critically, and process communication skills creatively. Through this PKM activity, which covers material on narrative texts, it can help, increase reading interest and narrative literacy skills of class 10 high school students at SMA N 1 Amanuban Selatan, increase students' understanding of the structure, characteristics and techniques of writing narrative texts. Develop students' skills in producing narrative texts creatively.